The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1080/716100343
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and the Challenge of Terminal Illness

Abstract: One of the assumptions that underpins the literature on spirituality is the belief that facing a terminal illness is a life crisis that intensifies the search for meaning, leaving individuals predisposed to embrace religion. To date, however, there is scant empirical research on the topic. This article seeks to make a contribution to this topic by reporting findings from a qualitative study that address the question of whether individuals embrace religious beliefs when faced with the challenge of a serious ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 35 publications
2
82
0
Order By: Relevance
“…They strove to maintain roles, as found by McGrath (2003). They perceived themselves foremost within roles they always held, rather than as patients.…”
Section: Discussionmentioning
confidence: 92%
“…They strove to maintain roles, as found by McGrath (2003). They perceived themselves foremost within roles they always held, rather than as patients.…”
Section: Discussionmentioning
confidence: 92%
“…She believes that her findings highlight the importance of maintaining a clear distinction between religion and a more generalized notion of spirituality, that is, finding meaning. 54,55 Palliative care researchers may make this distinction more frequently than other researchers who typically have measured spirituality and religiosity in terms of religious affiliation. Of 1117 empirical studies published in five palliative medicine/hospice journals, researchers assessed spirituality using variables such as spiritual well-being, meaning or transcendence (32%), followed by religious affiliation (29%), and spiritual/religious services provided (19%).…”
Section: What Is Spirituality?mentioning
confidence: 98%
“…She found that most did not seek explicitly religious comfort in response to their illness and that there was a degree of eclecticism in the religiospiritual concepts expressed by participants. 32 In a comparative study of cancer survivors and hospice patients, McGrath concluded that maintaining an intimate connection with life through family, friends, leisure, home, and work was just as important to individuals as transcendent meaning-making, religious or otherwise. 33 Palliative care researchers have increasingly recognized the importance of examining spiritual dimensions of end-of-life experience.…”
Section: Spirituality and Existentialismmentioning
confidence: 99%